2015
DOI: 10.1016/j.brainres.2014.09.064
|View full text |Cite
|
Sign up to set email alerts
|

A fruitful endeavor: Modeling ALS in the fruit fly

Abstract: For over a century Drosophila melanogaster, commonly known as the fruit fly, has been instrumental in genetics research and disease modeling. In more recent years, it has been a powerful tool for modeling and studying neurodegenerative diseases, including the devastating and fatal amyotrophic lateral sclerosis (ALS). The success of this model organism in ALS research comes from the availability of tools to manipulate gene/protein expression in a number of desired cell-types, and the subsequent recapitulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 293 publications
(505 reference statements)
2
70
1
1
Order By: Relevance
“…A brief overview only of the major results obtained in recent years with these models will be given here and the reader is referred to excellent recent reviews for more detailed accounts on the progress made in modelling specific diseases [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A brief overview only of the major results obtained in recent years with these models will be given here and the reader is referred to excellent recent reviews for more detailed accounts on the progress made in modelling specific diseases [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Several models of neurodegeneration have been developed with overexpression of disease proteins in the fly eye, given the ease of observing its structural degenerative phenotypes. Many studies have shown that overexpression of human TDP-43 in the fly eye results in an age-and dosedependent degeneration [5]. Reduction or overexpression of dTDP-43 in all fly neurons or within larval or adult motor neurons, the relevant cell type for ALS patients, results in decreased locomotion and adult lifespan [5].…”
mentioning
confidence: 99%
“…Many studies have shown that overexpression of human TDP-43 in the fly eye results in an age-and dosedependent degeneration [5]. Reduction or overexpression of dTDP-43 in all fly neurons or within larval or adult motor neurons, the relevant cell type for ALS patients, results in decreased locomotion and adult lifespan [5]. Several groups have reported disrupted synaptic morphology and defective synaptic transmission when TDP-43 levels are altered strictly within motor neurons, suggesting that endogenous TDP-43 may function to regulate synaptic physiology [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a Drosophila model of ALS expressing human TDP-43 (hTDP-43) (46), the transgenic fruit flies have progressive neurological degeneration characterized by brain cell death, progressive motor impairment, and a substantially reduced lifespan (25,46). Using this model, one group found that hTDP-43 selectively expressed in the flies' glial cells, but not when selectively expressed in neurons, caused a Drosophila endogenous retrovirus similar to HERV type K, named gypsy, to be expressed in higher quantities.…”
Section: Pre-clinical Modelsmentioning
confidence: 99%